STRATEGI KEPALA PERPUSTAKAAN DALAM MENUMBUHKAN MINAT BACA - Muhammad Soni Amrulloh (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
The more we read books, the more knowledge we have. On the other hand, the less we read books, the more limited our knowledge becomes. The potential of the Indonesian nation is very large when viewed from the number of its population consisting of various tribes, diverse cultures and languages ​​that need to be preserved. However, the huge potential in terms of quantity needs to be balanced with the quality it possesses. The first fact, UNESCO mentions that Indonesia ranks second from the bottom in terms of world literacy, meaning that reading interest is very low. According to UNESCO data, the reading interest of the Indonesian people is very concerning, only 0.001%. This means that out of 1,000 Indonesians, only 1 person is an avid reader. A different research entitled World Most Literate Nations Ranked conducted by Central Connecticut State University in March 2016, Indonesia was stated to be ranked 60th out of 61 countries regarding reading interest, just below Thailand (59) and above Botswana (61). Ironically, although interest in reading books is low, wearesocial data as of January 2017 reveals that Indonesians can stare at gadget screens for approximately 9 hours a day. Not surprisingly, in terms of fussiness on social media, Indonesians are ranked 5th in the world. Whereas Somadayo explained that every aspect of life involves reading.In fact, the public’s interest in reading, especially children as students, is currently still low. The low interest in reading in the community is closely related to the level of education in the country. According to the Law of the Republic of Indonesia Number 43 of 2007 concerning Libraries, the culture of fondness for reading is carried out through families, educational units, and the community with cooperation between the government in an effort to increase interest in reading, where the government acts as the main person in charge and the librarian performs optimally. The development of reading interest is continuously improved in order to form a society with a reading culture.